If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 2x + 25 Reorder the terms: -3 + 4x = 2x + 25 Reorder the terms: -3 + 4x = 25 + 2x Solving -3 + 4x = 25 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 4x + -2x = 25 + 2x + -2x Combine like terms: 4x + -2x = 2x -3 + 2x = 25 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 2x = 25 + 0 -3 + 2x = 25 Add '3' to each side of the equation. -3 + 3 + 2x = 25 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 25 + 3 2x = 25 + 3 Combine like terms: 25 + 3 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| 8x+34=18 | | (2)(3.14)(r)=7.41 | | 63+d=105 | | 16a+17b+4c+5c-5b-4a= | | (9+8)=68X | | 9x=3x-2 | | 18p+11q+p-4q-3p= | | -2x-3=4x+2 | | 2x+(3x/4)=11 | | 2X+2X=68 | | myles=lie | | 4(x^2+6)=168 | | 10y^7+35y^6+25y^5= | | 9-5y=37+2y | | 2x^2=-4+6x | | 500=6x^3+5x^2 | | 2x^2=-4+6 | | 10x+8=4x+25 | | 12m+4n-6m+9n= | | Wow=suchCake | | 6x^2+54=108 | | 2(9X)+2(8X)=68 | | roman=lie | | 18(t-6)+3t=7(3t+2)-8 | | X+2x+4=34 | | 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 | | 16(3x-4)=4(12x+1) |